Honeypot : Black Southern Women Who Love Women - Johnson, E. Patrick, 1967- (Book collections on Project MUSE., 2019)
"E. Patrick Johnson's Honeypot opens with the fictional trickster character Miss B. barging into the home of Dr. EPJ, informing him that he has been chosen to collect and share the stories of her people. With little explanation, she whisks the reluctant Dr. EPJ away to the women-only world of Hymen, where she serves as his tour guide as he bears witness to the real-life stories of queer black women throughout the American South. The women he meets come from all walks of life and recount their experiences on topics ranging from coming out and falling in love to mother/daughter relationships, religion, and political activism. As Dr. EPJ hears these stories, he must grapple with his privilege as a man and an academic, and in the process gains insights into patriarchy, class, sex, gender, and the challenges these women face. Combining oral history with magical realism and poetry, Honeypot is an engaging and moving book that reveals the complexity of identity while offering a creative method for scholarship to represent the lives of other people in a rich and dynamic way."--Provided by publisher.